Appendix to the article: Country Competitiveness and Investment Allocation in the Mining Industry: A survey of the literature and new empirical - Vásquez Cordano, Arturo (2021)
This Appendix is a complement of the article “Country Competitiveness and Investment Allocation in the Mining Industry: A survey of the literature and new empirical evidence".